KAPASITAS PERIKANAN CANTRANG DI PELABUHAN PERIKANAN PANTAI TEGALSARI KOTA TEGAL PROVINSI JAWA TENGAH PADA PENGELOLAAN PERIKANAN DEMERSAL - Budiarti, Tri Wahyu; Nurani, Tri Wiji; Wiyono, Eko Sri; Zulkarnain; Wudianto (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2024)
Demersal fish resources are one of the main commodities in the waters of the Java Sea. Tegalsari coastal fishing port is one of the fish landing locations around the Java Sea where most of the demersal commodities landed at the port were caught by cantrang fishing gear. Generally, every fishing activity expects ideal catches by using an efficient input. Technical efficiency can be used as an indicator of performance measurement of fishing gear. This study aimed to determine the fishing capacity of cantrang fisheries in Tegalsari fishing port. The fishing capacity analysis was carried out using fish landing data from PPP Tegalsari from 2008 to 2019. The measurement of technical efficiency by using the DEA (Data Envelopment Analysis) approach. The result showed that fishing capacity in 2013, 2015, 2017, 2018, and 2019 have to be maintained because it is in a fully utilized, and the rest of them were overcapacity caused by an excess capacity of the value of fishing gear and number of efforts. Keywords: Data Envelopment Analysis, Decision Making Unit, fish resources, fishing efficiency, Java Sea-Indonesia